Effectiveness of a modern landfill liner system in controlling groundwater quality of an open hydrogeological system, SE Lithuania - Baltrūnas, Valentinas; Slavinskienė, Gintarė; Karmaza, Bronislavas; Pukelytė, Violeta (Journal of Environmental Engineering and Landscape Management, 2020)
The work analyzes data of environmental geological mapping, groundwater monitoring of the region municipal waste landfill. This study examines the effectiveness of a modern landfill liner system in minimizing migration of pollutants in the groundwater of an open hydrogeological system. The results showed that dissolution of carbonates and dilution were the major processes controlling groundwater quality. In the landfill’s direct impact zone, groundwater was only weakly polluted with biogenic components. Increase in concentrations of these chemical components in this zone was related with the groundwater and surface runoff water flowing from adjacent areas. We can state that the modern landfill liner system we analysed is efficient and has no adverse effects on groundwater quality under hydrogeological conditions favourable for the spread of pollutants. However, in case of an accident, pollutants might pose a great threat on the safety of groundwater. Therefore, even modern landfill liner systems are not recommended to be constructed in open hydrogeological systems.